2001
DOI: 10.1002/ijc.10093
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer incidence and estrogen receptor α in normal mammary tissue—An epidemiologic study among Japanese women in Japan and Hawaii

Abstract: We have undertaken a study to examine whether the difference in breast cancer incidence between 2 populations of similar genetic background is reflected in a similar pattern of estrogen receptor ␣ expression in normal mammary gland. Study participants were 92 Japanese women from Sapporo, Japan (mean age 48.2 years) and 49 Japanese women from Honolulu, Hawaii (mean age 45.4 years), who underwent biopsy indicating normal breast tissue or benign, nonproliferative breast disease in hospitals in Sapporo, Japan and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…In an editorial accompanying this study, the authors found the results intriguing, but also pointed out some limitations of the study and the need for additional investigations (8). Since then, the results of two partially overlapping ecological studies in Asia (9, 10) were interpreted as compatible with those of the analytical investigation previously undertaken by Khan and colleagues (7). No study based on individuals however, using an approach similar to that of Khan and colleagues (7), has been reported, possibly because such an investigation presents considerable practical difficulties.…”
Section: Introductionsupporting
confidence: 79%
“…In an editorial accompanying this study, the authors found the results intriguing, but also pointed out some limitations of the study and the need for additional investigations (8). Since then, the results of two partially overlapping ecological studies in Asia (9, 10) were interpreted as compatible with those of the analytical investigation previously undertaken by Khan and colleagues (7). No study based on individuals however, using an approach similar to that of Khan and colleagues (7), has been reported, possibly because such an investigation presents considerable practical difficulties.…”
Section: Introductionsupporting
confidence: 79%
“…The same group of investigators then compared ERa expression in Japanese women in Hawaii with those in Japan, and found non-significantly higher levels in the Hawaiian Japanese, again in agreement with their higher breast cancer risk (Lawson et al 2002). Finally, there are now several studies documenting the increase in the proportion of ERa-expressing cells seen in proliferative breast lesions (Jacquemier et al 1982, Shoker et al 1999.…”
Section: Variability Of Naf Hormones Over Timementioning
confidence: 68%
“…The regulation works by estrogen receptor (ER) and progesterone receptor (PR) binding the receptors in the breast cell. ER and PR play an important role in the incidence of breast cancer; normal breast tissue of ER-positive expression will increase the risk of breast cancer [20]. ER and PR were closely related to the prognosis and endocrine therapy.…”
Section: Discussionmentioning
confidence: 99%